Penerapan Asas Contra Legem Perkara Nafkah Iddah Dalam Cerai Talak Pegawai Negeri Sipil: Studi Putusan No.135/Pdt.G/2022/MS.Ttn - Qodri, Jamalul; Lubis, Fauziah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Case No.135/Pdt.G/2022/MS/Ttn is a divorce case filed by the husband because it cannot be defended anymore. One of the consequences is that the husband is burdened to pay maintenance, namely madhiyah, iddah, and mut'ah. A wife can apply to the Panel of Judges to request payment of maintenance if the husband does not fulfill his obligation to provide. This research aims to find out the judge's consideration by not giving 1/3 of the salary to the ex-wife who is divorced by a husband who works as a civil servant. Whereas as in Government Regulation No. 8 of 1983 jo Government Regulation No. 45 of 1990 the wife gets 1/3 of the salary of the husband who is a civil servant after the divorce. This research is a type of library research and uses a statutory approach (statue approach) case approach and uses an analytical descriptive method and uses a deductive mindset. Legal materials consist of primary legal materials, namely decision No.135/Pdt.G/2022/MS/Ttn, Marriage Law Number 1 of 1974, Compilation of Islamic Law, Government Regulation No.10 of 1983 jo Government Regulation No. 45 of 1990. The result of this research is that the Judge does not issue 1/3 husband's salary based on Government Regulation No. 8 of 1983 jo Government Regulation No. 45 of 1990 to the divorced ex-wife. With consideration because the Respondent/wife is also a civil servant. The judge prioritizes the principle of justice for the community that is not a civil servant. Keywords: Contra Legem, Civil Servant, Iddah Maintenance.